2021
DOI: 10.36740/wlek202103220
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Satisfaction With Dental Care (On the Results of Sociological Research)

Abstract: The aim: To determine the level of patients' satisfaction with the received dental care in regional dental clinic and to make proposals for improving the quality of dental care based on the survey results. Materials and methods: 221 copies of the questionnaires completed by the respondents; sociological method (questionnaire), medical-statistical, analysis and bibliosemantic methods were used. Results: Patients expressed high satisfaction with the quality of dental care according to the criteria of geographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Results of a survey showed that, when compared to participants who felt their oral health was good, those who rated their oral health as poor found the high cost of dental care to be the most discouraging issue (P = 0.05) [8]. Results of another survey concluded that, compared to other aspects of healthcare quality, patients' satisfaction with the financial accessibility of dental care was shown to be lower [30].…”
Section: Costmentioning
confidence: 99%
“…Results of a survey showed that, when compared to participants who felt their oral health was good, those who rated their oral health as poor found the high cost of dental care to be the most discouraging issue (P = 0.05) [8]. Results of another survey concluded that, compared to other aspects of healthcare quality, patients' satisfaction with the financial accessibility of dental care was shown to be lower [30].…”
Section: Costmentioning
confidence: 99%